Flushed away - Bowers, David, 1970-; Fell, Sam; Kramer, Cecile; Sproxton, David; Garger, Maryann; Lord, Peter, 1953-; Clement, Dick; La Frenais, Ian; Lloyd, Christopher, 1960-; Keenan, Joe, 1958-; Davies, William (Screenwriter); Jackman, Hugh; et al. (Glendale, CA DreamWorks Animation SKG Home Entertainment, 2007)
Roddy is a decidedly upper-crust "society mouse" who lives the life of a pampered pet in a posh Kensington flat. When a sewer rat named Sid comes out of the sink, he decides he had hit the jackpot. Roddy schemes to rid himself of Sid by luring him into the "whirlpool." Sid may be an ignorant slob, but he's no fool, but it is Roddy who winds up being flushed away into the bustling sewer world of Ratropolis. There Roddy meets Rita, an enterprising scavenger who works the sewers in the Jammy Dodger, her faithful boat. Roddy immediately wants out, or rather, up. Trouble comes in the form of the villainous Toad -- who royally despises all rodents. The Toad dispatches his two hapless hench-rats, Spike and Whitey, to get the job done. When they fail, the Toad has no choice but to send to France for his cousin, Le Frog, the dreaded mercenary.
Special features: Widescreen version -- 21 games and challenges (including Soccer showdown, Belched away, Sludge buster, Ice maker, Disco Le Frog) -- All-new animated slug songs -- Learn to build a slug.
DVD release of the 2006 motion picture.
Widescreen.
Special features: filmmaker commentary ; new animated slug songs ; The music of Flushed away ; Meet the cast ; Flushed away tunes ; Build a slug ; Learn to draw Roddy ; A maze of pipes ; DVD-ROM: "Flushed away underground adventure" game ; "A maze of pipes" game ; build-a-slug.
Directors of photography, Brad Blackbourn, Frank Passingham ; editors, Eric Dapkewicz, John Venzon ; original music, Harry Gregson-Williams ; costume designer, Jane Poole ; production designer, David A.S. James ; visual effects supervisor, Wendy Rogers ; animators, Manuel Almela, Chris Capel, Greg Whittaker ; co-producer, Maryann Garger.
Hugh Jackman, Kate Winslet, Ian McKellen, Jean Reno, Bill Nighy, Andy Serkis, Shane Richie.
MPAA rating: PG; for crude humor and some language.
Keywords: Ragpickers -- London (England) -- Drama; Mice as pets -- Juvenile films; Rattus norvegicus -- England -- London -- Juvenile films; Sewerage -- England -- London -- Juvenile films; Cousins -- Juvenile films; Villains in motion pictures; Kensington (London, England) -- Juvenile drama; Juvenile works; Villains in motion pictures; Adventure films; Animated films -- 2007.; Comedy films; Feature films -- 2007.; Video recordings for the hearing impaired; Films for the hearing impaired; Feature films; Children's films; Action and adventure films